Anti corruption system in Malaysia and Singapore: a comparative study / Arsidah Arhan, Kent Audrey L. Kading and Roshayati Radellah. - Arhan, Arsidah; L. Kading, Kent Audrey; Radellah, Roshayati (2008)
The main purpose of this legal study is to review and also examine the weaknesses of the anti-corruption system in Malaysia, with Singapore being the comparison country, as well as proposing some suggestion on how the system in Malaysia can be improve. This study was based on secondary sources which obtained from the Law Library of Universiti Teknologi MARA (UiTM) as well as legislation, articles from the newspaper, cases, internet and also reliable sources which are related to corruption. The scope of this study confined only to the legislation body and also agencies from Malaysia and Singapore, thus, the comparative studies will not refer to any countries except for the two countries. This study is basically a comparison between Malaysia and Singapore anti-corruption system whereby the legislation and anti-corruption agencies are the main subjects that were examined and observed. At the end of this study, the researchers have identified the weaknesses of Malaysian anti-corruption system and had come up with some recommendations in order to improve such weaknesses. Therefore, it is hoped that this legal study will provide a comprehensive discussion over the anti-corruption system in both countries and hopefully it can be a benchmark in proposing a model that can improve the system in Malaysia.